2019
DOI: 10.1002/adma.201903615
|View full text |Cite
|
Sign up to set email alerts
|

Adlayer‐Free Large‐Area Single Crystal Graphene Grown on a Cu(111) Foil

Abstract: To date, thousands of publications have reported chemical vapor deposition growth of “single layer” graphene, but none of them has described truly single layer graphene over large area because a fraction of the area has adlayers. It is found that the amount of subsurface carbon (leading to additional nuclei) in Cu foils directly correlates with the extent of adlayer growth. Annealing in hydrogen gas atmosphere depletes the subsurface carbon in the Cu foil. Adlayer‐free single crystal and polycrystalline single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
90
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 82 publications
2
90
0
Order By: Relevance
“…Copper has stable electronic configuration which limits its reaction with C atoms to weak forces and reduces the bulk diffusion of C atoms in Cu substrate [21]. This gives copper an advantage in growing single layer graphene, where the process progresses on the surface [21,139]. Experimenting with different metal substrates, copper soon raised as an excellent substrate for CVD growth of Graphene [38,91,[138][139][140].…”
Section: Solid Substratesmentioning
confidence: 99%
See 3 more Smart Citations
“…Copper has stable electronic configuration which limits its reaction with C atoms to weak forces and reduces the bulk diffusion of C atoms in Cu substrate [21]. This gives copper an advantage in growing single layer graphene, where the process progresses on the surface [21,139]. Experimenting with different metal substrates, copper soon raised as an excellent substrate for CVD growth of Graphene [38,91,[138][139][140].…”
Section: Solid Substratesmentioning
confidence: 99%
“…This gives copper an advantage in growing single layer graphene, where the process progresses on the surface [21,139]. Experimenting with different metal substrates, copper soon raised as an excellent substrate for CVD growth of Graphene [38,91,[138][139][140]. Early work by Li et al found that the low C solubility of copper at high temperatures reduces precipitation on the surface and results in more uniform single-layer graphene growth [38].…”
Section: Solid Substratesmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 Nowadays the most widely used approach for large-scale graphene synthesis is the chemical vapor deposition (CVD) method using Cu as the substrate, [10][11][12][13] but due to the low solubility of C in Cu and the necessity of Cu to catalyze the decomposition of methane (CH 4 ), the CVD growth of graphene on Cu is usually self-limited, i.e., MLG-dominant films are obtained. 10,14 However, these MLG films are usually decorated with few-layer graphene (FLG) regions. This is due to that, at the beginning of CVD growth, when a graphene layer nucleates on Cu surface, simultaneous growth of more layers (adlayers) underlying this layer usually starts as well.…”
Section: Introductionmentioning
confidence: 99%